2019
DOI: 10.1002/ange.201901478
|View full text |Cite
|
Sign up to set email alerts
|

A Ligand‐Protected Golden Fullerene: The Dipyridylamido Au328+ Nanocluster

Abstract: A golden fullerene Au32 cluster has been synthesized with amido and phosphine ligands as the protecting agents. Single‐crystal X‐ray structural analysis revealed that this gold nanocluster, [Au32(Ph3P)8(dpa)6] (SbF6)2 (Hdpa=2,2′‐dipyridylamine), has a stable pseudo‐Ih Au328+ core with S6 symmetry, which features an Au12@Au20 Keplerate cage co‐protected by Ph3P and dpa ligands. Quantum‐chemical studies were conducted to elucidate the origin of the special stability of this cluster, and suggest that it is electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…21−25 It is well-known that the capping ligands have a significant effect on properties of NCs. In the past few decades, different kinds of ligands have been investigated to stabilize NCs, such as thiols, 26,27 phosphines, 28−31 carbine 32 and nitrogen ligands, 33 alkynyl ligands, 34 etc. 35 Recently, hydrides, as the protected ligands, have been used in the syntheses of NCs.…”
mentioning
confidence: 99%
“…21−25 It is well-known that the capping ligands have a significant effect on properties of NCs. In the past few decades, different kinds of ligands have been investigated to stabilize NCs, such as thiols, 26,27 phosphines, 28−31 carbine 32 and nitrogen ligands, 33 alkynyl ligands, 34 etc. 35 Recently, hydrides, as the protected ligands, have been used in the syntheses of NCs.…”
mentioning
confidence: 99%
“…111 In addition to isolating Au 25 (SG) 18 nanoclusters, the representative Au m (PPh 3 ) n clusters also reacted with hydrophobic ligands and gave the corresponding hydrophobic nanoclusters. For example, Shichibu et al reported identical ligand exchange reactions between Au 11 (PPh 3 ) 8 Cl 2 and n-alkanethiols C n H 2n+1 SH (n = 2, 8, 10,12,14,16,18) and achieved rod-like [Au 25 (PPh 3 ) 10 (SC n H 2n+1 ) 5 Cl 2 ] 2+ , 101 for which the configuration was resolved by single-crystal X-ray diffraction (Fig. 1B).…”
Section: Ligand Exchange-induced Size/structure Transformationsmentioning
confidence: 93%
“…Collectively, the effects of steric hindrance and the electronic effect of introduced ligands played a dominant role in tailoring the surface coordination environments, core/shell structures, and stabilities of metal nanoclusters, despite there is no necessary relationship between the type of ligands and the structures of the nanoclusters in the direct preparation method. 13,14 For example, for the Au 32 cluster case, changing the peripheral ligands would not alter the overall molecular framework of the nanocluster. 13,14 However, owing to their different stabilizers, the two Au 32 nanoclusters also displayed ligand-dependent electronic structures (i.e., the electron densities and optical absorptions).…”
Section: Advantages and Challenges Of Leistmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, except for the non-hollow icosahedral M 1 @M 12 kernel (M represents the metal), the hollow icosahedral M 12 kernel has also served as a basic nano-building block of nanoclusters (e.g., Ag 44 (SR) 30 , Au 12+n Cu 32 (SR) 30+n , Ag 50 (dppm) 6 (SR) 30 , Au 144 (SR) 60 , etc.) 10,11,[52][53][54][55][56] . Structurally, it is accepted that the non-hollow icosahedron might be more energetically favorable than the corresponding hollow one due to the extra 12 metal•••metal interactions in M 1 @M 12 ; accordingly, the hollow icosahedral kernel is unlikely to arise in the initial stage of the nanocluster growth.…”
mentioning
confidence: 99%